Activation of Educational Research Fundamentals in the Light of Knowledge Society Requirements: A Future Vision - Ali Abdel-Raouf Mohammed Nassar (University of Science and Technology, Yemen, 2015)
Building knowledge society imposes many challenges that cast a shadow on educational research because it is responsible for the formation of educational knowledge system that considered to be one of the tributaries of the knowledge society. In spite of the efforts that have been made to promote educational research to build knowledge society, there are weaknesses and shortcomings in the output of educational research reduce its contribution in solving educational problems, as well as weakness in its contributions to the development of educational process itself, which considered to be the basis upon which the processes of absorption, the production and dissemination of knowledge. These processes are essential for building knowledge society. The present study aimed at providing a future vision in activating elements of educational research to meet the requirements of the knowledge society. The study employed descriptive approach to achieve its objective, as one of future studying methods, Delphi technique was also utilized in the study, a questionnaire was applied to a group of experts of faculty members at education faculties. A set of results were emerged of the present study. The study found that educational research can contribute in building knowledge society where there has the necessary ingredients, including absorption of educational knowledge through scientific training of researchers and faculty members at faculties of education, the production of knowledge in order to ensure educational building real communities of knowledge, and the application of educational knowledge by employing the findings of the educational research in developing reality of educational practices. In the light of the results of study, a future vision was proposed to activate the elements of educational research to meet the requirements of the knowledge society. This vision is based on a set of principles and premises, it also seeks to achieve several objectives through a number of procedures and mechanisms. the study provided a set of recommendations in relation to the application of the proposed vision.  Keywords: Educational Research, knowledge society, the future vision.